Salinity change effects on growth and photosynthetic efficiency of the zooxanthellae Symbiodinium sp. extracted from Platygyra daedalea in Qatar coral reefs - Ayesha Siddiqua (6269193) (2025)
This study investigates the impact of elevated salinity levels on the growth and photosynthetic efficiency of the coral endosymbiont Symbiodinium sp. isolated from Platygyra daedalea in the coral reefs of Qatar. Cultures were exposed to a range of salinities (30–70 psu) over a 11-day incubation period under controlled laboratory conditions. Results revealed a significant decline in cell density and growth rate at salinities above 55 psu. Photosynthetic performance, assessed using the OJIP chlorophyll fluorescence protocol, showed a marked reduction in key parameters—including ABS/RC, DIo/RC, TRo/RC, ETo/RC, Vi, Vj, Mo, and Fv/Fm—at salinities exceeding 55 psu, indicating substantial stress and inactivation of PSII reaction centers. Interestingly, a partial recovery in photosynthetic efficiency was observed at 55 and 60 psu following initial decline. This is the first study to examine the physiological response of Symbiodinium sp. to salinity stress in the Arabian Gulf, providing valuable insights for coral reef restoration initiatives in this high-salinity environment amid ongoing climate change and coastal development. Other Information Published in: Marine Pollution Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.marpolbul.2025.118187